Onset Age and Clinical Heterogeneity of Dementias: A Diagnostic and Therapeutic Approach - Serrano, Cecilia M. (2014)
Frontotemporal dementia (FTD) is the main differential diagnosis with early stages of Alzheimer’s disease (AD). Usually, differential diagnosis between a first depressive episode and the beginning of an early degenerative dementia with mood disorders, either AD or FTD, can be difficult. Objective: To evaluate the clinical characteristics of patients with senile and presenile onset dementia, to compare their neuropsychiatric and neuropsychological profiles according to onset age and to provide clinical approach. Methods: A two year prospective-retrospective study was conducted. All patients were evaluated with a complete neuropsychiatric and neuropsychological battery, laboratory tests and neuroimaging. Healthy control subjects were also studied. Results: Included 366 subjects were divided into over or under 65 years old, and then matched for educational level. AD was the most common cause of dementia in subjects over 65 years of age, followed by depression and FTD. Subjects younger than 65 years old, showed higher prevalence of depression followed by FTD, AD, and finally primary progressive aphasia (PPA). At younger ages, the highest severity of cognitive impairment, behavioral disorder and major depression were observed. Conclusion: Onset age of cognitive and/or behavioral impairment may be one of the variables influencing the clinical heterogeneity of dementias. Many of the young-onset dementias may be potentially reversible so, its early identification and pathophysiology understand, increase pharmacological intervention opportunities of halting the cascade of events that lead inexorably to dementia. In the new era of biomarkers, their help in identifying each clinical phenotype could encourage their best use in clinical practice and help selecting more accurate pharmacological treatment.